Transsynaptic linking of calcium channels and postsynaptic receptors at a dyadic synapse - Jian Zhao; Evan Ardiel; Stephen Nurrish; Joshua M. Kaplan (Proceedings of the National Academy of Sciences, 2026)
Polyadic synapses (where each active zone is juxtaposed with multiple postsynaptic targets) are found in many brain regions and are implicated in learning and memory, yet little is known about how they function. To address this question, we analyze Caenorhabditis elegans cholinergic (ACh) motor neurons, which form dyadic synapses with two targets (a body muscle and a GABAergic motor neuron). Decreasing ACh receptors in either target elicits a retrograde decrease in presynaptic type 2 voltage-activated calcium channels (CaV2), thereby decreasing ACh release. By contrast, blocking GABA motor neuron differentiation (thereby eliminating one target) results in ectopic clustering of GABA A receptors at ACh neuromuscular junctions, which elicits a retrograde increase in presynaptic strength. These results suggest that presynaptic CaV2 channels are linked to postsynaptic receptors in both targets, which allows each target to modify transmission to both targets.